Survey of Antagonistic Action and the Mechanism of these Actions that Terpens, Phenols and their Derivatives Possess Against Different Pathogenic Agents - Muayyed Najem, Ali (Al-Nahrain Journal of Science, 2021)
Folk medicine or herbal treatment has been used for centuries by different ancient civilizations against various ailment agents, herbal medicine has been dragged attention by researchers in different medical branches focusing on therapeutically characteristic features of each plant against different pathogenic agents responsible for most devastating and terrifying diseases, in addition to thorough investigation for the phytochemical compounds in each plant responsible for its potent against pathogens. Thus, this study highlights on two major groups of secondary metabolic compounds: terpens, phenols and their derivatives as antimicrobial agents against different bacterial and fungal strains especially drug resistant bacteria which responsible for the infectivity of treatments of most infectious diseases. Furthermore, mechanisms of actions of these secondary metabolites are reviewed as the causative factors responsible for the antimicrobial activity of plants and the promising results which have been achieved in multiply these activities by making combination between these natural products and chemical drugs.